Adaptive Homeostatic Strategies of Resilient Intrinsic Self-Regulation in Extremes (RISE): A Randomized Controlled Trial of a Novel Behavioral Treatment for Chronic Pain - Kent, Martha; Mardian, Aram S.; Regalado-Hustead, Morgan Lee; Gress-Smith, Jenna L.; Ciciolla, Lucia; Kim, Jinah L.; Scott, Brandon A. (Frontiers in Psychology, 2021)
Current treatments for chronic pain have limited benefit. We describe a resilience intervention for individuals with chronic pain which is based on a model of viewing chronic pain as dysregulated homeostasis and which seeks to restore homeostatic self-regulation using strategies exemplified by survivors of extreme environments. The intervention is expected to have broad effects on well-being and positive emotional health, to improve cognitive functions, and to reduce pain symptoms thus helping to transform the suffering of pain into self-growth. A total of 88 Veterans completed the pre-assessment and were randomly assigned to either the treatment intervention (n = 38) or control (n = 37). Fifty-eight Veterans completed pre- and post-testing (intervention n = 31, control = 27). The intervention covered resilience strengths organized into four modules: (1) engagement, (2) social relatedness, (3) transformation of pain and (4) building a good life. A broad set of standardized, well validated measures were used to assess three domains of functioning: health and well-being, symptoms, and cognitive functions. Two-way Analysis of Variance was used to detect group and time differences. Broadly, results indicated significant intervention and time effects across multiple domains: (1) Pain decreased in present severity (F(1, 56) = 5.02, p < 0.05, η2p=.08), total pain over six domains (F(1, 56) = 14.52, p < 0.01, η2p=.21), and pain interference-decrease (F(1, 56) = 6.82, p < 0.05, η2p=.11); (2) Affect improved in pain-related negative affect (F(1, 56) = 7.44, p < 0.01, η2p=.12), fear (F(1, 56) = 7.70, p < 0.01, η2p=.12), and distress (F(1, 56) = 10.87, p < 0.01, η2p=.16); (3) Well-being increased in pain mobility (F(1, 56) = 5.45, p < 0.05, η2p=.09), vitality (F(1, 56) = 4.54, p < 0.05, η2p=.07), and emotional well-being (F(1, 56) = 5.53, p < 0.05, η2p=.09 Mental health symptoms and the cognitive functioning domain did not reveal significant effects. This resilience intervention based on homeostatic self-regulation and survival strategies of survivors of extreme external environments may provide additional sociopsychobiological tools for treating individuals with chronic pain that may extend beyond treating pain symptoms to improving emotional well-being and self-growth.